Spatial Dynamics of Land Cover Change of Gag Island, Indonesia - Rifai, Ahmat; Rakuasa, Heinrich; Latue, Philia Christi (Westscience Press, 2025)
Gag Island in Raja Ampat Regency, Southwest Papua, has experienced significant land cover change due to intensive nickel mining activities since 2017, transforming tropical forest into open land with serious ecological and socio-economic impacts. This study analyzed the spatial dynamics of land cover change using 3-meter resolution PlanetScope satellite imagery (2017, 2021, 2025) through visual classification in ArcGIS Pro, with four land cover classes: settlement, open area, mining, and forest/garden. Results show an expansion of mining area from 4.53 hectares (2017) to 301.13 hectares (2025), accompanied by a decrease in mixed forest from 5,898.37 hectares to 5,576.21 hectares, and an increase in sedimentation that threatens coastal ecosystems and coral reefs. The discussion reveals contradictions between mining permit policies and small island protection regulations, as well as recommendations for high-resolution image-based monitoring and sustainable reclamation to mitigate impacts. This study provides a scientific basis for sustainable natural resource management on small islands with high conservation value.